Über Rudolf Fuchs’ Letztes unvollendetes Projekt im Londoner Exil: Der Deutsche Almanach aus der Tschechoslowakei - Kountouroyanis, Konstantin (Brünner Beiträge zur Germanistik und Nordistik, 2023)
After Rudolf Fuchs fled Prague for London following the 1938 Munich Agreement, he embarked on the task of compiling an almanac featuring German-speaking authors from Czechoslovakia. This endeavor continued until shortly before his accidental death in 1942. The article explores Fuchs' motivation for pursuing this intended publication. It investigates the almanac's purpose, the selection of authors and texts, and the criteria that texts and authors had to meet to be included in the almanac.